The 2021 European Alliance of Associations for Rheumatology/American College of Rheumatology Points to Consider for Diagnosis and Management of Autoinflammatory Type I Interferonopathies: CANDLE/PRAAS, SAVI, and AGS. Issue 5 (21st March 2022) - Cetin Gedik, Kader; Lamot, Lovro; Romano, Micol; Demirkaya, Erkan; Piskin, David; Torreggiani, Sofia; Adang, Laura A.; Armangue, Thais; Barchus, Kathe; Cordova, Devon R.; Crow, Yanick J.; Dale, Russell C.; et al.
Abstract : Objective: Autoinflammatory type I interferonopathies, chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature/proteasome‐associated autoinflammatory syndrome (CANDLE/PRAAS), stimulator of interferon genes (STING)–associated vasculopathy with onset in infancy (SAVI), and Aicardi‐Goutières syndrome (AGS) are rare and clinically complex immunodysregulatory diseases. With emerging knowledge of genetic causes and targeted treatments, a Task Force was charged with the development of "points to consider" to improve diagnosis, treatment, and long‐term monitoring of patients with these rare diseases. Methods: Members of a Task Force consisting of rheumatologists, neurologists, an immunologist, geneticists, patient advocates, and an allied health care professional formulated research questions for a systematic literature review. Then, based on literature, Delphi questionnaires, and consensus methodology, "points to consider" to guide patient management were developed. Results: The Task Force devised consensus and evidence‐based guidance of 4 overarching principles and 17 points to consider regarding the diagnosis, treatment, and long‐term monitoring of patients with the autoinflammatory interferonopathies, CANDLE/PRAAS, SAVI, and AGS. Conclusion: These points to consider represent state‐of‐the‐art knowledge to guide diagnostic evaluation, treatment, and management of patients with CANDLE/PRAAS, SAVI, and AGS and aim to standardize and improve care, quality of life, and disease outcomes.